University extension: a teaching-learning experience that helps to develop the abilities and skills of law students - da Silva, Renan Antônio [UNESP] (Centro Universitario La Salle - UNILASALLE, 2023)
The paper discusses the development of students’ skills and abilities in Brazil. The model of legal education centered on the teacher´s theoretical presentation in the classroom gave way to the forms of knowledge construction that reserve to the student an active and participative place in the teaching and learning process. The study of laws, doctrine and jurisprudence remains essential for the technical training of the Bachelor of Law if it is carried out to form a critical and reflective spirit. In this participatory learning process, university extension plays a decisive role, since it favors the development of a citizen consciousness and more active and transformative posture, including activities of “teaching with research” and “action research”. The concrete teaching experience refers to an extension project that aims to turn more effective the right of access to justice of people who live around the public university where the author operates.
A extensão universitária: uma experiência de ensino-aprendizagem que ajuda desenvolver as habilidades e competências dos estudantes de direito
Keywords: Apprenticeship; Extensionist activity; Law courses; Teaching with research. Action research